TINGKAT KEPUASAN KONSUMEN â€œSOP BUAH ICAâ€ DI BOULEVARD MANADO - Chichi S.T. Kansil; Grace A.J Rumagit; Charles R. Ngangi; Ellen G. Tangkere (Universitas Sam Ratulangi, 2015)
SUMMARYChichi Srijayanti Tamaweol Kansil. Level of Costumer Satisfaction Ica Fruit Soup in Boulevard Manado (Guidance of Grace A. J. Rumagit as chairman, Charles R. Ngangi and Ellen G. Tangkere, as members).The objectives of this research is to analyze the level of costumer satisfaction based on aspects of product, price, place and services in Ica Fruit Soup, and to know the effort that will take to maintain and to improve those four aspects in face the dynamic of this business competition.The research is conducted over three months from November 2014 until February 2015, started from preparation until undergraduation exams. The data used in the form of primary data and secondary data. The used Sampling is accidental technique sampling that is sample based on chance, anyone by chance met with researchers can be used as a sampel. Samples were taken for one week and obtained a total sample of 93 people .The analysis is done using a likert scale and followed by analysis of costumer satisfaction index.The result showed that consumer satisfy about the aspect of product by average score of 79.60 percent, consumers satisfy about the aspect of price by average score of 75.70 percent, consumers satisfy enough about the aspect of place by average score of 64.5 percent, while the aspect of service is consumer satisfy by average score of 68.4 percent.Keywords : Consumer Satisfaction, Product, Price, Place and Service